Investigation of tenderness mechanisms in calcium-enhanced muscle - Lawrence, T.E.; Stephens, J.W.; Obuz, E.; Davis, J.R.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We explored the mechanism(s) of calcium- induced tenderization in calcium-enhanced beef muscle. At 72 hours postmortem, we injected (9% by weight) beef strip loins (n=15) with 0, 0.05, 0.1, 0.2, or 0.4 M calcium chloride (CaCl2) with and without 0.05 M zinc chloride (ZnCl2), and they were then aged until 15 days postmortem. Warner- Bratzler shear force peak values indicated that addition of ZnCl2 drastically inhibited tenderization; however, enhancement with CaCl2 still tended to reduce shear values (P=0.07; 0.55 kg) when ZnCl2 was present. In the absence of ZnCl2, the 0.2 and 0.4 M CaCl2 treatments were 18.9 and 32.1% more (P<0.05) tender than the no CaCl2 treatment. These results suggest that both calcium-activated enzymatic activity and a non-enzymatic salting-in effect contributed to tenderization of calcium-enhanced muscle. However, the enzymatic mechanism reduced toughness 2.9 to 7.5 fold more than the non-enzymatic mechanism. Calcium-activated enzymatic degradation appears to be the major tenderization mechanism, and non-enzymatic salting-in of calcium ions appears to be a minor tenderization mechanism, even at high calcium concentrations.
Keywords: Beef; Tenderness; Calcium-enhanced muscle